2014
DOI: 10.3109/01443615.2014.985768
|View full text |Cite
|
Sign up to set email alerts
|

Management of hydrosalpinx before IVF: A literature review

Abstract: Hydrosalpinx has a detrimental effect on the outcome of in vitro fertilization (IVF). Surgical intervention such as salpingectomy or tubal occlusion before IVF improves the outcome of IVF, but these procedures are often contraindicated in women with dense pelvic adhesions. Thus, it is worthwhile to search minimally invasive alternative therapies. The main objective of this review is to assess and compare the value of all the therapeutic options for hydrosalpinx before IVF. The results of the following procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…Hydrosalpinx is found in about 10–30% of women with infertility due to tubal factors, corresponding to approximately 5% of infertile women. Apart from the primary effect on fertility, hydrosalpinx is also associated with a large reduction (about 40–50%) in pregnancy rates, following in‐vitro fertilization embryo transfer (IVF‐ET), and an increased risk of miscarriage and heterotopic pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrosalpinx is found in about 10–30% of women with infertility due to tubal factors, corresponding to approximately 5% of infertile women. Apart from the primary effect on fertility, hydrosalpinx is also associated with a large reduction (about 40–50%) in pregnancy rates, following in‐vitro fertilization embryo transfer (IVF‐ET), and an increased risk of miscarriage and heterotopic pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…During the last few years, some researchers have tested this device in non‐randomized studies as an alternative treatment for hydrosalpinx, before ET. These micro‐inserts avoid the need for laparoscopic surgery and anesthesia and its potential complications, especially in patients with pelvic adhesions or endometriosis, or who are not good surgical candidates for laparoscopy. However, insertion of Essure is not free of risk, either perioperative or reproductive, for example, it can lead to fluid accumulation in the endometrial compartment.…”
Section: Introductionmentioning
confidence: 99%
“…Other less invasive and safer treatment modalities for patients with hydrosalpinx undergoing IVF-ET include ultrasound guided aspiration of hydrosalpinx uid and hysteroscopic occlusion of fallopian tube with Essure micro-inserts. Although the initial results of these treatment modalities are promising, their routine use in the management of patients with hydrosalpinx undergoing IVF-ET is not recommended because their supporting evidence was obtained from small studies [7][8][9]. Moreover, ultrasound guided aspiration of hydrosalpingeal uid may cause aring of pelvic infection or injury of bowel and cannot be used in patients with hydrosalpinges which are not visible by ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ultrasound guided aspiration of hydrosalpingeal uid may cause aring of pelvic infection or injury of bowel and cannot be used in patients with hydrosalpinges which are not visible by ultrasound. Similarly, hysteroscopic occlusion of fallopian tube with Essure micro-inserts delays IVF cycle, may cause injury of uterus and may be associated with long term complications such as menstrual irregularities, allergy and chronic pelvic pain [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The Practice Committee of the American Society for Reproductive Medicine in collaboration with The Society of Reproductive Surgeons concluded "…of six women with hydrosalpinx, after pretreatment at least one will get pregnant before IVF" [7]. Currently, pretreatments for hydrosalpinx include salpingectomies, salpingostomies, proximal tubal ligation, ultrasound-guided hydrosalpinx aspiration, and interventional tubal occlusion [8][9][10][11][12]. A recent Cochrane review concluded that laparoscopic salpingectomy or tubal occlusion before IVF increases the probability of pregnancy [5].…”
Section: Introductionmentioning
confidence: 99%